Male Involvement in Maternal Health Care at Anomabo, Central Region, Ghana - Craymah, Joshua Panyin; Oppong, Robert Kwame; Tuoyire, Derek Anamaale (International Journal of Reproductive Medicine, 2017)
Background. Globally, male involvement in maternal health care services remains a challenge to effective maternal health care accessibility and utilization. Objective. This study assessed male involvement in maternal health care services and associated factors in Anomabo in the Central Region of Ghana. Methods. Random sampling procedures were employed in selecting 100 adult male respondents whose partners were pregnant or had given birth within twelve months preceding the study. Pearson Chi-Square and Fisher’s exact tests were conducted to assess the association of sociodemographic and enabling/disenabling factors with male involvement in maternal health care services. Results. Some 35%, 44%, and 20% of men accompanied their partners to antenatal care, delivery, and postnatal care services, respectively. Male involvement in antenatal care and delivery was influenced by sociodemographic (partner’s education, type of marriage, living arrangements, and number of children) and enabling/disenabling (distance to health facility, attitude of health workers, prohibitive cultural norms, unfavourable health policies, and gender roles) factors. Conclusion. The low male involvement in maternal health care services warrants interventions to improve the situation. Public health interventions should focus on designing messages to diffuse existing sociocultural perceptions and health care provider attitudes which influence male involvement in maternal health care services.